Membrane stiffness and myelin basic protein binding strength as molecular origin of multiple sclerosis - Benjamin Krugmann (Nature Portfolio, 2020)
Abstract Myelin basic protein (MBP) and its interaction with lipids of the myelin sheath plays an important part in the pathology of multiple sclerosis (MS). Previous studies observed that changes in the myelin lipid composition lead to instabilities and enhanced local curvature of MBP-lipid multilayer structures. We investigated the molecular origin of the instability and found that the diseased lipid membrane has a 25% lower bending rigidity, thus destabilizing smooth $$>1\,$$ > 1 µm curvature radius structures such as in giant unilamellar vesicles. MBP-mediated assembling of lipid bilayers proceeds in two steps, with a slow second step occurring over many days where native lipid membranes assemble into well-defined multilayer structures, whereas diseased lipid membranes form folded assemblies with high local curvature. For both native and diseased lipid mixtures we find that MBP forms dense liquid phases on top of the lipid membranes mediating attractive membrane interactions. Furthermore, we observe MBP to insert into its bilayer leaflet side in case of the diseased lipid mixture, whereas there is no insertion for the native mixture. Insertion increases the local membrane curvature, and could be caused by a decrease of the sphingomyelin content of the diseased lipid mixture. These findings can help to open a pathway to remyelination strategies.